2019
DOI: 10.1038/s41598-019-55210-x
|View full text |Cite
|
Sign up to set email alerts
|

Diel changes and diversity of pufM expression in freshwater communities of anoxygenic phototrophic bacteria

Abstract: The anoxygenic phototrophic bacteria (APB) are an active component of aquatic microbial communities. While DNA-based studies have delivered a detailed picture of APB diversity, they cannot provide any information on the activity of individual species. Therefore, we focused on the expression of a photosynthetic gene by APB communities in two freshwater lakes (Cep lake and the Římov Reservoir) in the Czech Republic. First, we analyzed expression levels of pufM during the diel cycle using RT-qPCR. The transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 68 publications
(90 reference statements)
2
26
0
Order By: Relevance
“…In support of the true photoheterotrophic nature of Gemmatimonadota, a previous study conducted in Rímov Reservoir, found active expression of their pufM genes (a common molecular marker gene for aerobic anoxygenic phototrophs) (27). Expression of the photosynthetic apparatus of Gemmatimonadota showed that they are an active part of bacterial community and do not just passively contain the phototrophic genes (27).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In support of the true photoheterotrophic nature of Gemmatimonadota, a previous study conducted in Rímov Reservoir, found active expression of their pufM genes (a common molecular marker gene for aerobic anoxygenic phototrophs) (27). Expression of the photosynthetic apparatus of Gemmatimonadota showed that they are an active part of bacterial community and do not just passively contain the phototrophic genes (27).…”
Section: Discussionmentioning
confidence: 90%
“…It has been suggested that Gemmatimonadota may be relatively more abundant in dry soils ( 26 ). On the other hand, from the available data, it is known that they are also present in aquatic environments, such as freshwater lakes ( 27 ), sediments ( 22 , 28 30 ), and estuaries ( 31 , 32 ). In addition, G. phototrophica was isolated from a freshwater lake in Inner Mongolia ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…The higher light intensity in OL and OL-Inh treatments compared to LL treatment could favor photoheterotrophic bacteria, such as AAP bacteria, whose growth efficiency has been documented to be enhanced by light both in the laboratory and in marine waters (26,27,41). In agreement with this assumption, proteobacterial ASVs in the total bacterial community affiliated with genera known to contain AAP bacterial species, such as Limnohabitans, Polynucleobacter (Burkholderiales), and Roseomonas (Rhodospirillalles) (31,44), were also found to be relatively abundant members of the AAP community ( Fig. 4B and 5B).…”
Section: Discussionmentioning
confidence: 59%
“…S4B) indicates that some "bottle effect" may have occurred. On the other hand, Verrucomicrobiota and Alphaproteobacteria (including the order Caulobacterales), which showed the highest increase in relative abundance throughout the experiment, were reported to be the most active groups based on 16S rRNA amplicon libraries constructed from the transcript in a mesocosm experiment conducted at the same time in the Ř ímov Reservoir (44). Thus, although we were not able to completely exclude the "bottle effect" from our enclosures, we conclude that the observed changes in total bacterial and AAP communities resulted predominantly from their response to the manipulation of primary production and less from the "bottle effect" per se.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation